Efficacy and safety of maintenance and reliever combination budesonide/formoterol therapy in asthma patients at risk of severe exacerbations: a randomised controlled trial - Patel, Mitesh Dilipkumar Kantilal (2013)
The Single combination budesonide/formoterol inhaler as Maintenance And Reliever Therapy (SMART) regimen reduces severe asthma exacerbations, but it is uncertain whether it increases the risk of adverse effects due to high corticosteroid and beta-agonist doses with both short-term and cumulative exposure in patients at risk of severe exacerbations. The primary hypothesis was that the SMART regimen would reduce the risk of beta-agonist overuse. Secondary aims were to investigate whether patients treated with the SMART regimen were less likely to seek medical review in the setting of beta-agonist overuse and to determine whether any reduction in severe asthma exacerbations would be at a cost of a higher systemic corticosteroid burden.